Candida urinary tract infections in adults - ODABAŞI, ZEKAVER (SPRINGER, 2020)
Candiduria is commonly seen in hospitalized patients and most of the patients are asymptomatic, but it may be due to cystitis, pyelonephritis, prostatitis, epididymo-orchitis or disseminated candidiasis. Major risk factors are diabetes mellitus, indwelling urinary catheters, use of broad-spectrum antibiotics, urinary obstruction, and admission to intensive care units. Candida urinary tract infections can be caused by hematogenous spread following candidemia, or retrograde route via the urethra. The presence of Candida species in urine in asymptomatic patients does not warrant antifungal therapy except neutropenic patients, very low-birth-weight infants and patients undergoing urologic procedures. Fluconazole is the treatment of choice for symptomatic infections, it achieves high urinary levels. The other azole antifungals and echinocandins do not reach sufficient urine levels. Amphotericin B deoxycholate is the alternative antifungal agent if fluconazole can not be used because of resistance, allergy or failure.
Keywords: Candiduria; Funguria; Candida; Candida urinary tract infection; Fluconazole; Amphotericin B; CRITICALLY-ILL PATIENTS; RISK-FACTORS; MANAGEMENT; COLONIZATION; URETEROSCOPY; EPIDEMIOLOGY; ASSOCIATION; DIAGNOSIS; SCORE; BALL